Multilocus sequence typing analysis and molecular characterization of carbapenemase related genes in Acinetobacter baumannii isolated from hospitalized patients in Erbil city, Iraq: Carbapenemase-related genes in A. baumannii - Abduljabar , Khelat Adhem; Mawlood, Ahang Hasan (Cellular and Molecular Biology, 2023)
Acinetobacter baumannii, has been recognized by (WHO) as a global priority pathogen. It has been demonstrated to quickly pick up antimicrobial resistance genes. Multilocus sequence typing (MLST) is an unambiguous typing method for identifying accurate and portable nucleotide sequences of internal fragments of multiple housekeeping genes. The present study aimed to determine the sequence type using MLST, genetically define the carbapenem resistance phenotype and clarify the epidemiology of multidrug resistant (MDR) A. baumannii in the Kurdistan region of Iraq. Clinical samples were collected from ICU patients. VITEK 2 compact system was used for bacterial identification and antimicrobial susceptibility profile. PCR was used for detecting carbapenemase-related genes. Additionally, MLST was used to evaluate the genetic diversity of carbapenem-resistant isolates using Oxford scheme primers. In this investigation, 63 non-duplicate A. baumannii isolates from hospitalized patients were identified. According to CLSI standards, 75% and 73.4% of isolates were resistant to meropenem and imipenem respectively. Tigecycline and colistin were the most effective antibacterial agents. Of the various combinations of carbapenemase genes identified, the most common co-existence of genes present among clinical isolates were BlaOXA-23, and BlaOXA-51 (95.31%). While the less common combination of genes was detected in 4 isolates (6.25 %) consisting of the co-existence of all tested carbapenemase genes in the present study (BlaOXA-23, BlaOXA-51, BlaOXA-58, BlaIMP, BlaVIM, BlaNDM). Regarding MLST analysis, the results confirmed that ST 556 (n=4) had the greatest frequency rate among clinical isolates, followed by ST 218 (n=3). Notably, the most common worldwide clonal lineage was CC92, which corresponded to (ICII). Only two isolates from ST 441, on the other hand, matched CC109/ ICI. The present investigation revealed a significant level of diversity among A. baumannii isolates.